2021
DOI: 10.1038/s42003-021-02707-9
|View full text |Cite
|
Sign up to set email alerts
|

Widespread loss of mammalian lineage and dietary diversity in the early Oligocene of Afro-Arabia

Abstract: Diverse lines of geological and geochemical evidence indicate that the Eocene-Oligocene transition (EOT) marked the onset of a global cooling phase, rapid growth of the Antarctic ice sheet, and a worldwide drop in sea level. Paleontologists have established that shifts in mammalian community structure in Europe and Asia were broadly coincident with these events, but the potential impact of early Oligocene climate change on the mammalian communities of Afro-Arabia has long been unclear. Here we employ dated phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…We note that the two diversity troughs detected for African and European sirenian lineages ( Fig. 6 )—near the EOB and during the early Oligocene—are similar to the pattern presented by de Vries et al (2021) for African terrestrial mammals.…”
Section: Discussionsupporting
confidence: 76%
“…We note that the two diversity troughs detected for African and European sirenian lineages ( Fig. 6 )—near the EOB and during the early Oligocene—are similar to the pattern presented by de Vries et al (2021) for African terrestrial mammals.…”
Section: Discussionsupporting
confidence: 76%
“…Evolutionary model fitting revealed that the two most-integrated traits (brain shape and dental morphology) followed the same trajectory, but that trajectory differed across guilds. Brain shape and dental morphology evolved under stabilising selection in folivores and following a BM process in frugivores, signalling the selective pressures acting during the phenotypic evolution of folivorous strepsirrhines and the ancestral frugivorous state in Strepsirrhini [ 25 , 28 , 49 ]. Our results suggest that adapting to insectivory correlated with directional selection in brain shape, the only guild with such a pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Comprising more than 120 living species, they exhibit intermediate relative brain size between non-primate mammals and more derived anthropoids [ 8 , 9 ], and a variety of dietary and foraging specialisations that are reflected in their dental morphology [ 25 27 ]. Strepsirrhines are thought to have diversified in continental Africa, experiencing an early Oligocene partial extinction event, followed by colonisation of Madagascar, perhaps in two independent events [ 28 , 29 ]. Once in Madagascar, strepsirrhines diversified to fill a range of dietary niches (including folivory, frugivory, gummivory and insectivory) and specialise for different activity periods [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a particular DNE value of the occlusal surface of a tooth (or tooth-like buccal elements in conodonts) should reflect a particular diet. However, DNE has, until now, been only used to analyze skeletal parts of mammals, especially primate teeth (Bunn et al 2011; Godfrey et al 2012; Winchester et al 2014; Prufrock et al 2016; Berthaume and Schroer 2017; López-Torres et al 2018; Pampush et al 2019; Fulwood 2020; Li et al 2020; Cuesta-Torralvo et al 2021), but also those of marsupials (Lang et al 2022), carnivorans (hyenas, bears) (Pérez-Ramos et al 2020; de Vries et al 2021; Lang et al 2022), scandentians (tree shrews) (Selig et al 2019), rodents (Prufrock et al 2016; Renaud and Ledevin 2017; Vermeer 2019; de Vries et al 2021), chiropterans (Pellegrom 2019; López-Aguirre et al 2022; Villalobos-Chaves and Santana 2022), multituberculates (Robson 2018), artiodactyls (suids) (Rannikko et al 2020), eulipotyphles (hedgehogs) (Vitek et al 2021), and one mammal stem group (Harper et al 2019). DNE is defined in such a way that it is independent of scale.…”
Section: Introductionmentioning
confidence: 99%